Faktor-Faktor yang Berhubungan dengan Kunjungan Balita di Posyandu Karya Bhakti Wilayah Kerja Puskesmas Paduan Rajawali Kabupaten Tulang Bawang - Alfa Sukmawati; Hikmah Ifayanti; Iis Tri Utami (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Posyandu is a vital community health service for monitoring toddler growth and development; however, toddler visits remain low. Data from the Indonesian Ministry of Health (2024) shows toddler weighing coverage in Lampung at 80.4%, with Paduan Rajawali Health Center achieving 85.1% in 2023, declining to 80.3% in 2024. Low attendance impacts malnutrition detection, stunting risk, and child development. A pre-survey in the area identified maternal knowledge, occupation, husband’s support, and perception as influential factors. This study aims to analyze factors associated with toddler visits to Karya Bhakti Posyandu to improve child health. Quantitative methods with an analytical cross-sectional design were used. The population included all mothers with toddlers aged 12–59 months (160), with a sample of 62 respondents using random sampling. The dependent variable was posyandu visits; independent variables were maternal knowledge, occupation, economic status, and perception. Data were collected via questionnaires and analyzed using univariate and bivariate (chi-square) analysis. Results showed most mothers at Karya Bhakti Posyandu had good knowledge (54.8%), informal employment (71%), and high economic status (62.9%). Positive perception reached 51.6%, with 56.5% routinely bringing toddlers to posyandu. Bivariate analysis revealed significant associations between maternal knowledge (p = 0.039) and perception (p = 0.005) with toddler visits, while occupation (p = 0.133) and economic status (p = 0.421) were not significant. Recommendations: Posyandu should offer engaging activities and active outreach by cadres. Mothers are encouraged to increase knowledge and consistently bring toddlers. The village should provide continuous information dissemination. Future researchers may explore other factors affecting toddler visits.